Current perspective on the role of insulin and glucagon in the pathogenesis and treatment of type 2 diabetes mellitus - Ojha A; Ojha U; Mohammed R; Chandrashekar A; Ojha H (Dove Medical Press, 2019)
Ashutosh Ojha,1 Utkarsh Ojha,2 Raihan Mohammed,3 Abhinaya Chandrashekar,2 Harsh Ojha41Shobhaben Pratapbhai Patel School Of Pharmacy & Technology Management, SVKM’s Narsee Monjee Institute of Management Studies, Mumbai, India; 2Faculty of Medicine, Imperial College London, London, UK; 3Department of Medicine, University of Cambridge, Cambridge, UK; 4Department of Life Sciences, University of Warwick, Coventry, UKAbstract: According to the World Health Organization, 422 million adults worldwide live with diabetes mellitus (DM), a significant portion of whom have type 2 diabetes. The discovery of insulin as a key regulator of glucose metabolism has revolutionized our understanding of DM and provided several therapeutic avenues. Most studies have so far predominantly focused on the role of insulin in type 2 diabetes. However, the balance between insulin and glucagon is essential in ensuring glucose homeostasis. In this review, we begin by evaluating the principal differences between insulin and glucagon with regard to their mechanism and control of their secretion. Next, we discuss their mode of action and effects on metabolism. We further explore how the two hormones impact the natural history of type 2 diabetes. Finally, we outline how current and emerging pharmacological agents attempt to exploit the properties of insulin and glucagon to benefit patients with type 2 diabetes.Keywords: type 2 diabetes mellitus, insulin, glucagon, glucose